Natural and Synthetic Saponins as Vaccine Adjuvants - Pengfei Wang (Vaccines, 2021)
Saponin adjuvants have been extensively studied for their use in veterinary and human vaccines. Among them, QS-21 stands out owing to its unique profile of immunostimulating activity, inducing a balanced Th1/Th2 immunity, which is valuable to a broad scope of applications in combating various microbial pathogens, cancers, and other diseases. It has recently been approved for use in human vaccines as a key component of combination adjuvants, e.g., AS01b in Shingrix® for herpes zoster. Despite its usefulness in research and clinic, the cellular and molecular mechanisms of QS-21 and other saponin adjuvants are poorly understood. Extensive efforts have been devoted to studies for understanding the mechanisms of QS-21 in different formulations and in different combinations with other adjuvants, and to medicinal chemistry studies for gaining mechanistic insights and development of practical alternatives to QS-21 that can circumvent its inherent drawbacks. In this review, we briefly summarize the current understandings of the mechanism underlying QS-21’s adjuvanticity and the encouraging results from recent structure-activity-relationship (SAR) studies.